2020
DOI: 10.2147/dnnd.s224912
|View full text |Cite
|
Sign up to set email alerts
|

<p>Re-Evaluating the Use of IFN-β and Relapsing Multiple Sclerosis: Safety, Efficacy and Place in Therapy</p>

Abstract: The advent of interferon therapy for the treatment of multiple sclerosis (MS) was a massive advancement in the field and changed the course of the disease. While the exact mechanism of interferon therapy in MS is unknown, disease control is likely mediated by reducing Th1 and Th17 cells while increasing regulatory T cells and altering the cytokine profile. Interferon therapy not only gave physicians and patients an evidence-based treatment option to treat MS by decreasing relapses and the accrual of disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…IFNβ was first approved for treatment of relapsing remitting multiple sclerosis in 1993 after showing an 18-34% reduction in relapse rate. The efficacy for IFNβ was considered to be due suppression of viral infections that are associated with relapses and to direct immunomodulatory effects that include reduction of pathogenic Th1 and Th17 CD4+ T cells, and to increases in IL-10 producing T reg cells ( 87 ). All these may be mediated by increased expression of PD-L1 (CD274), an ISG that in mice is more responsive to IFNβ due to its high receptor affinity ( 88 ).…”
Section: Therapeutic Uses Of Type I Interferonmentioning
confidence: 99%
“…IFNβ was first approved for treatment of relapsing remitting multiple sclerosis in 1993 after showing an 18-34% reduction in relapse rate. The efficacy for IFNβ was considered to be due suppression of viral infections that are associated with relapses and to direct immunomodulatory effects that include reduction of pathogenic Th1 and Th17 CD4+ T cells, and to increases in IL-10 producing T reg cells ( 87 ). All these may be mediated by increased expression of PD-L1 (CD274), an ISG that in mice is more responsive to IFNβ due to its high receptor affinity ( 88 ).…”
Section: Therapeutic Uses Of Type I Interferonmentioning
confidence: 99%
“…Furthermore, they have a major role in the activation of key natural host cells, such as Natural Killer (NK) cells and dendritic cells (DC) (reviewed in [12] ). Of interest, IFN-β exerts stronger anti-inflammatory effects with respect to IFN-α, inducing reduction of pathogenic Th17 CD4 + T cells and increase in IL-10 producing Treg cells [13] . Moreover, IFN-β inhibits the production of TGF-β, thought to be involved in lung fibrosis and other inflammatory responses [14] .…”
Section: The Early Cytokine and Cellular Response To Sars-cov-2 Infectionmentioning
confidence: 99%
“…No observed drawbacks were associated with IFN-β administration except lymphopenia. [55,56] Studies regarding the IFN-β antiviral COVID-19 replication are suggested to be effective through activating Janus kinases (JAKs) pathways leading to activated antiviral and antiproliferative actions. [57,58] It was severally reported an increase in COVID-19 neurological manifestations as a drawback of IFN-β administration in infected patients.…”
Section: The Impact Of Immunotherapies In Managing Neurological Manifmentioning
confidence: 99%
“…[57,58] It was severally reported an increase in COVID-19 neurological manifestations as a drawback of IFN-β administration in infected patients. [55][56][57] Remdesivir is a promising nucleoside antiviral analog drug currently used in controlling COVID-19 delirium complications. [59,60] Although Remdesivir has been widely used in COVID-19 treatment protocols, no significant clinical or antiviral effective actions were observed.…”
Section: The Impact Of Immunotherapies In Managing Neurological Manifmentioning
confidence: 99%